1998
DOI: 10.1080/036107398244300
|View full text |Cite
|
Sign up to set email alerts
|

Serum Cholesterol Levels as a Measure of Frailty in Elderly Patients

Abstract: The authors evaluated the association between serum cholesterol levels and social, clinical, and functional characteristics in 637 elderly hospitalized patients (mean age = 79.1 years, range = 65-97) from the Geriatric Evaluation and Rehabilitation Unit (GERU) at P. Richiedei Hospital in Gussago, Brescia (Italy). Patients consecutively admitted to the GERU during an 18-month period underwent a multidimensional evaluation including information on demographics, cognitive status, physical health (number of chroni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(18 citation statements)
references
References 23 publications
3
15
0
Order By: Relevance
“…The association between low levels of LDL-C and an increased risk of all cause mortality could be explained by reverse causation. Debilitation and illness have been hypothesised to cause a decrease in levels of cholesterol 18 19 and, in this study, comorbidities were more frequent in individuals with the lowest levels of LDL-C. Also, consistent with the theory that low levels of LDL-C are an indirect marker of severe disease, the association between low levels of LDL-C and the risk of all cause mortality was strongest in the age and sex adjusted model, and substantially reduced when adjusting for baseline comorbidities. An association remained after this adjustment, however, and after excluding individuals with less than five years of follow-up and known cardiovascular disease, cancer, and chronic obstructive pulmonary disease at baseline.…”
Section: Discussionmentioning
confidence: 99%
“…The association between low levels of LDL-C and an increased risk of all cause mortality could be explained by reverse causation. Debilitation and illness have been hypothesised to cause a decrease in levels of cholesterol 18 19 and, in this study, comorbidities were more frequent in individuals with the lowest levels of LDL-C. Also, consistent with the theory that low levels of LDL-C are an indirect marker of severe disease, the association between low levels of LDL-C and the risk of all cause mortality was strongest in the age and sex adjusted model, and substantially reduced when adjusting for baseline comorbidities. An association remained after this adjustment, however, and after excluding individuals with less than five years of follow-up and known cardiovascular disease, cancer, and chronic obstructive pulmonary disease at baseline.…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings between total cholesterol and function outcomes post-stroke have been observed previously, 8 and other research suggests that a low cholesterol may be a marker of frailty and poor nutritional status in older age. 27 …”
Section: Discussionmentioning
confidence: 99%
“…The relationships between lipid profiles and frailty have rarely been explored [11]. In a study on 637 hospitalized old patients, Ranieri et al concluded that lower serum cholesterol levels were an independent hematologic marker of frailty [27]. Low cholesterol level is a marker of malnutrition and could therefore be noncausally associated with frailty status.…”
Section: Discussionmentioning
confidence: 99%